O impacto das distâncias institucionais na sobrevivência de subsidiárias estrangeiras - Souza, Fábio Cássio de (2016)
The survival of the subsidiary is an important indicator of the success of foreign investments. Several studies focus efforts on survival testing. The institutional approach emerges as an alternative research topic. However, they are generally restricted to few national institutional distances. This research is intended to contribute to the literature examining the impact of nine institutional distances (ID) on the survival of subsidiary in a different continent than the parent. In addition, it investigates the local experience and its reducing national institutional distances. The hypotheses were tested in 1,650 observations of subsidiaries in 36 countries, in a longitudinal study in the period of 2007-2014. The hazard ratio was implemented with the Cox Regression for the execution. The models indicated effectiveness with a high degree of significance. The results suggest that national DIs have a significant impact on survival. Between the nine DI examined, six evidence of survival risk related to administrative aspects, demographic, political, knowledge, global and cultural. Local experience also plays a relevant role for continuity, however, it is not able to moderate DI for the survival of the subsidiary. It is hoped that this evidence can provide important information for the strategic process and contribute to the success and survival of international operations.